1.
"\\frac{3x-1}{(x+1)(x-3)}=\\frac{A}{x+1}+\\frac{B}{x-3}"
"\\frac{A}{x+1}+\\frac{B}{x-3}=\\frac{A(x-3)+B(x+1)}{(x+1)(x-3)}=\\frac{3x-1}{(x+1)(x-3)}"
"A(x-3)+B(x+1)=3x-1"
"Ax-3A+Bx+B=3x-1"
"(A+B)x-(3A-B)=3x-1"
"\\begin{alignedat}{2}\n A+B = 3 \\\\\n 3A-B = 1\n\\end{alignedat}" "\\begin{alignedat}{2}\n A = 1 \\\\\n B = 2\n\\end{alignedat}"
Answer
"\\frac{1}{x+1}+\\frac{2}{x-3}"
2. "\\frac{2}{3}+5=5\\frac{2}{3}=\\frac{17}{3}"
3. a. "4x^{2}+8x+1=0"
"x^{2}+2x+0.25=0"
"x^{2}+2x+1-1+0.25=0"
"(x+1)^{2}-0.75=0"
"(x+1)^{2}=0.75"
"x_{1}+1=\\sqrt{0.75}" "x_{2}+1=-\\sqrt{0.75}"
"x_{1}=\\sqrt{0,75}-1" "x_{2}=-\\sqrt{0,75}-1"
"x_{1}=\\frac{\\sqrt{3}}{2}-1" "x_{2}=-\\frac{\\sqrt{3}}{2}-1"
b. "3x^{2}+4x-3=0"
"x^{2}+\\frac{4}{3}x-1=0"
"x^{2}+\\frac{4}{3}x-1+\\frac{4}{9}-\\frac{4}{9}=0"
"(x+\\frac{2}{3})^{2}-\\frac{13}{9}=0"
"(x+\\frac{2}{3})^{2}=\\frac{13}{9}"
"x_{1}+\\frac{2}{3}=\\sqrt\\frac{13}{9}" "x_{2}+\\frac{2}{3}=-\\sqrt\\frac{13}{9}"
"x_{1}=\\frac{\\sqrt{13}-2}{3}" "x_{2}=-\\frac{\\sqrt{13}+2}{3}"
Comments
Dear M, thank you for a feedback.
the last problem has a condition error. to build a triangle you need 3 values and in the case of breathing 2
Leave a comment